Reducing Radiation Dermatitis Using a Film-forming Silicone Gel During Breast Radiotherapy: A Pilot Randomized-controlled Trial - AHN, SONGMI (In Vivo, 2020)
Background/Aim: To evaluate whether topical use of a film-forming silicone gel (StrataXRT(®)) could reduce radiation dermatitis compared to a moisturizing cream (X-derm(®)) in patients receiving whole breast radiotherapy. Patients and Methods: A total of 56 patients with breast cancer were randomized to use StrataXRT or X-derm. The severity of radiation dermatitis was graded using physiological skin parameters, clinician-assessed visual rating scales and patient-reported symptoms. Changes in these parameters from baseline to 4 weeks post-radiotherapy were evaluated every two weeks. Results: Two-way repeated-measures ANOVA revealed different patterns of changes in the erythema index (F=3.609, p=0.008) and melanin index (F=3.475, p=0.015). The post hoc analysis demonstrated a significantly lower erythema index and melanin index in the patients allocated to the StrataXRT group. Conclusion: The use of StrataXRT can reduce radiation dermatitis with respect to objectively measured physiological skin parameters. The results of the present study will support the feasibility of conducting a larger randomized controlled trial.